Qualidade da água e composição fitoplanctônica de um viveiro de piscicultura utilizado para fins de pesca esportiva e irrigação - Lachi, Giuliana Berchieri [UNESP]; Sipauba-Tavares, Lucia Helena [UNESP] (Inst Pesca, 2008)
Water quality of a fish pond used by UNESP, at Jaboticabal, SP, Brazil, for both fishing and irrigation has been evaluated according to certain limnological parameters and to its phytoplankton composition. During the year, four sampling sites were assigned at the pond: P(1)=inlet water in the pond; P(2)=inlet water from a shrimp pond; P(3)=irrigation spot; and P(4)=outlet water (water flowing directly into another pond). The collected data show a water pond with high concentration of nutrients and chlorophyll-a, and high values of electrical conductivity, total hardness and total dissolved solids, proceeding from the above pond. These factors affected substantially some biological parameters, such as chlorophyll-a and phytoplankton. In P(3), whereas class Zygnematophyceae showed the highest specimens richness, with 34.01%, the Chlorophyceae, that had the highest number of genera, comprehended 33.52% of the total number of individuals. The use of the water fish pond for irrigation must be re-evaluated, due to eutrophic conditions of the water, the presence of potentially toxic cyanobacteria, so as the proper management employed.
Water quality and phytoplankton composition in a sportsfishery and irrigation pond
Keywords: Aquaculture; Water quality; phytoplankton composition; limnological parameters; water exchange